Gut Microbial Communities of Social Bees - Kwong, Waldan K. (Nat Rev Microbiol, 2016)
The gut microbiota can have profound effects on hosts, but studying these relationships in humans presents challenges. The specialized gut community of honey bees parallels the mammalian microbiota, as both are mostly composed of host-adapted, facultative anaerobes and microaerophiles. The bee gut community, however, is far simpler, being dominated by only nine bacterial species clusters that are only associated with bees and that are transmitted through social interactions between individuals. Recent developments, including the discovery of extensive strain-level variation, evidence of protective and nutritional functions, and reports of eco-physiological or disease-associated community perturbations, have drawn attention to the microbiota’s role in bee health, as well as its potential as a model for studying gut symbiont ecology and evolution.